Influence of lightning current parameters and earthing system designs on tower footing impedance of 500 kV lines - Mohamad Nasir N.A.F.; Ab Kadir M.Z.A.; Osman M.; Abd Rahman M.S.; Ungku Amirulddin U.A.; Mohd Nasir M.S.; Zaini N.H.; Nik Ali N.H. (MDPI AG, 2023)
Electromagnetic fields; Lightning; Outages; Soils; Systems analysis; Towers; 500 kV transmission lines; Earthing system designs; High frequency operation; Lightning current parameters; Lightning performance; Low and high frequencies; Soil-structure analysis; Sustainable operations; Electric grounding